STRATEGI CORPORATE PUBLIC RELATIONS DALAM MEMPERTAHANKAN CITRA PRODUK INDIHOME TELKOM DI WITEL MAKASSAR - Shinta Haerunnisa Tosno , Nur; Hadawiah, Hadawiah; Majid , Abd (UNIVERSITAS MUSLIM INDONESIA, 2022)
Strategy corporate public relations is a management function that creates, maintains, and maintains good and beneficial relationships between an organization and the public that can influence the success or failure of the organization. This research is focused to find out about the strategy of the company's corporate public relations in maintaining the product image of IndiHome PT. Telkom at Witel Makassar and secondly to find out about the product image of IndiHome PT. Telkom Makassar in Minasa Upa Village, Rappocini District. The type of research used is descriptive qualitative research with data collection techniques in the form of observation, documentation, and interviews. By using three theories, namely Image Theory, Theory of Integration and Attitude Change, and Excellent Theory. This research lasted for approximately 1 month located on Jl. Balaikota No. 04 Makassar. The informants in this study were General Manager & GS, Customer Care Manager, Corporate Secretary of IndiHome Telkom Witel Makassar, and the community of Minasa Upa Village, Rappocini District, Makassar City. The results show that IndiHome Telkom Witel Makassar's strategy in maintaining its image is to continue to provide excellent service which is the main key to staying good in the eyes of its customers and the image of Telkom's IndiHome products in the eyes of the community, especially in Minasa Upa Village, Rappocini District is very diverse.